1989
DOI: 10.1136/bmj.298.6689.1673
|View full text |Cite
|
Sign up to set email alerts
|

Damp housing, mould growth, and symptomatic health state.

Abstract: Widespread administration of anti-D immunoglobulin antenatally in this regimen would not be possible at present because of limited supply from a decreasing pool of immunised donors. Immunoglobulin produced by genetic engineering, however, may be available soon, and trials are planned to study the effectiveness of even lower doses. When studying a treatment regimen for any side effects it is important to avoid the bias created by considering only untoward consequences. Unexpected benefits are also possible, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
245
4
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(264 citation statements)
references
References 10 publications
6
245
4
5
Order By: Relevance
“…Householders appeared to have an increased sense of control, self esteem and a more positive sense of their home-effects best explained not simply as a consequence of the removal of negative conditions but rather of the introduction of positive changes at both a material and a psychosocial level. While research has pointed to the link between negative socio-economic conditions, including cold and poor physical health, and others have posited a link between poor living conditions and poor psycho-social outcomes (Hopton & Hunt, 1996;Khanom, 2000;Platt, Martin, Hunt, & Lewis, 1989), our findings suggest that relatively simple improvements to material circumstances have a positive impact not only on physical but also mental well-being. Beneficiaries of home energy improvements felt happier, more comfortable and more in control of their environment.…”
Section: Resultsmentioning
confidence: 50%
“…Householders appeared to have an increased sense of control, self esteem and a more positive sense of their home-effects best explained not simply as a consequence of the removal of negative conditions but rather of the introduction of positive changes at both a material and a psychosocial level. While research has pointed to the link between negative socio-economic conditions, including cold and poor physical health, and others have posited a link between poor living conditions and poor psycho-social outcomes (Hopton & Hunt, 1996;Khanom, 2000;Platt, Martin, Hunt, & Lewis, 1989), our findings suggest that relatively simple improvements to material circumstances have a positive impact not only on physical but also mental well-being. Beneficiaries of home energy improvements felt happier, more comfortable and more in control of their environment.…”
Section: Resultsmentioning
confidence: 50%
“…Numerous studies (primarily cross-sectional in design) involving older children and adults have reported at least one positive association between total airborne fungal or bacterial counts, or specific fungal taxa including Penicillium, Cladosporium, Aspergillus or Alternaria species, and respiratory symptoms including cough, wheeze and asthma (Platt et al, 1989;Strachan et al, 1990;Bjornsson et al, 1995;Li and Hsu, 1997;Garrett et al, 1998;Dharmage et al, 2001;Downs et al, 2001). Null findings in all age groups also have been reported for both airborne (Su et al, 2001) and dustborne fungi (Wickman et al, 1992;Verhoeff et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Objective methods such as air sampling, weight gain of wood blocks, or cultivation of spores from dust have been tested (36, 38, 49, 51-.S4), but only a modest agreement between objective sampling methods and questionnaires has been found (39,49,50). Most epidemiologic studies have relied on questionnaires completed by occupants to measure the presence of damp or mould, but evidence from two studies suggests that occupants are more likely to report their homes as having damp or mould than are research investigators, with as much as 30% disagreement (36,41), and a recent study suggests the opposite -that is, that occupants are less likely to report homes as being damp (50).…”
Section: Housing Characteristics Associated With Mould Growthmentioning
confidence: 99%
“…Fig. 3 shows the odds ratios for cough and wheeze in adults associated with damp and mould in the home (36,(43)(44)(45), and Fig. 4 shows the odds ratios for asthma in both children and adults (33,(39)(40)(41)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Association Between Indoor Damp or Mould Growth And Healthmentioning
confidence: 99%
See 1 more Smart Citation